OPTIMIZATION OF THE STUDY PROCESS ORGANIZATION IN THE STATE BORDER GUARD COLLEGE - Indriksons, Alens (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The present paper explores specificity of educational process in the State Border Guard College as a militarized educational institution. It is specific and implementation of educational process in such institution is not possible without the successive and continuous organization of the study process. The correct organization of the study process and scientific content of the training program serves as a basis for development of the students' theoretical knowledge and practical skills and its structural and content organization is essential for the implementation of a qualitative educational process. The aim of the research is to identify the possibilities to improve the structural and content based organization of the study process of the State Border Guard College in order to facilitate the achievement of the goals set by the border guard training process. The study was conducted in the State Border Guard College using scientific, pedagogical and psychological literature analysis and evaluation and document analysis research method. The author brought forward conclusion that the structural and content study process improving in the State Border Guard College can be achieved by changing professional border guard training course program (1 month) and professional further education study program "Border Guarding", study subjects and their succession.